Pengaruh Lokasi Terhadap Keputusan Berkunjung Wisatawan (Studi Kasus Objek Wisata Hutan Pinus Loji Lereng Kelud) - Novita Putri Diantanti; Isya Asrori (Universitas Islam Balitar, 2021)
The main problem of the case study to be investigated is whether there is an effect on the location of the decision to come to a tour of the kelud slopes loji pine forest. Meanwhile, the research objective is to know the effect of location on the decision to visit the Kelud Loji Slope Pine Forest Tourism. To obtain and in order to know the results, the researchers used descriptive methods, descriptive statistical tests, test instruments which included validity testing and reliability testing. Meanwhile, the classical assumption test includes normality test, autocorrelation test, heteroscedasticity test, and t test. The research was carried out starting from April 1 and ending on April 30, 2019 in the pine forest tourism slopes of the kelud village of Tulungrejo, Kec. Gandusari, Blitar Regency. After discussion, the result shows that the t value is 2.204 and the t table is 1.66 calculated from the two-tailed sig value is 5% (0.05), it can be concluded that the calculated T value is greater than the T table value, so it can be said that the location has an influence on the decision to visit tourists. Or the Ha value is accepted because T count is greater than the T table value and Ho is rejected because the T table value is not greater than the T count value. The conclusion in this study is that the location has an influence on the decision to visit a tourist attraction. Therefore, it is hoped that the manager will give more concepts to the tourism so that it is more developed.